STATE OF SCIENTIFIC DEVELOPMENT OF THE QUESTION OF SPECIAL KNOWLEDGE IN CRIMINAL PROCEEDINGS (Bulletin of criminological association of Ukraine, 2023)
In the article it has been emphasized that the development of effective methods of using special knowledge in criminal proceedings is impossible without their proper scientific development. It has been established that the concepts, signs, significance of special knowledge in criminal proceedings and tactical and forensic support for their use during pre-trial investigation are constantly the subject of scientific research. It has been noted that specialists in the fields of criminal procedure, forensics and forensics paid a lot of attention to special knowledge in criminal proceedings as an object of forensic research. In addition, the essence and significance of special knowledge in the judiciary were highlighted in their scientific works by administrative scientists, civil scientists, etc. It has been found that the content of scientific developments in the outlined area and their detailing differ depending on the set goals and level of scientific research. The analysis of the state of scientific development of the issue of special knowledge in criminal proceedings has been carried out taking into account the level systematization of scientific works: monographs and dissertations, scientific and practical publications, scientific articles and reports. It has been established that scientific works highlight both general theoretical provisions relating to the concept, signs and meaning of special knowledge, the specifics of their use in criminal proceedings depending on the form, etc., as well as the specifics of the use of special knowledge in criminal proceedings of a separate category or at certain stages thereof. It has been emphasized that there are no comprehensive studies of the use of special knowledge during the investigation of military crimes, which is why the indicated direction of scientific research is considered promising.
Keywords: special knowledge; use; criminal proceedings; scientific development; scientific works